ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERUBAHAN LABA PADA PDAM KABUPATEN SIKKA - Simo, Maria Herlina; Sayang, Sabulon; Marselina, Apriana (Program Studi Akuntansi Universitas Flores, 2020)
The purpose of this study is to analyze the factors that influence changes in profits in the regional water company (PDAM) Sikka regency. The factors studied are ROA (Return On Assets) and BOPO (Operational Costs on Operatig Income). The population used in this study is the vinacial statements in the Regional Draking Water Company (PDAM) of Sikka Regency, the sample In this study is the report of changes in profit or loss from 2015-2017 in the Regional Draking Water Company (PDAM) of Sikka Regency. The useful analytical tecthnique Is multiple lineal regression with a confidence level of 5%. Hipothesis testing using t-statistics to test the effect partially and f-statistics to test the effects simultaneously (together) where tested using SPSS Version 25 for windows. Based on the results of data analysis shows: (1) ROA (Return On Assets) partially significant effect on changes in erarnings with a tcount of 4417 with a significant level of 0.000<0.05, then the tecount table (4147>2035), (2) BOPO (Operational Costs on Operatig Income) partially significant effect on changes in erarnings with a tcount of 4547 and a significant level of 0,000<0.05, then thitunh label (4547>2035), (3) ROA (Return On Assets) and BOPO (Operational Costs on Operatig Income) partially influential and significant to changes in earnings with frinung value>Fubel (11,390>3.28) and a significant level of 0,000<0.0.